2005
DOI: 10.1111/j.0022-1112.2005.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Pikeperch habitat use within a canal network in spring

Abstract: Thirteen pikeperch Sander lucioperca were implanted with acoustic transmitters and 10 were successfully tracked twice a week from March to early July in a drainage canal connected to a brackish lagoon located in the Rhône delta. Pikeperch was found in the main canal and in narrow tributaries, but never in the lagoon. Pikeperch avoided shallow parts of the canal and selected areas with high riparian vegetation (mainly trees). No between sexes differences occurred in habitat selection. At the basin scale, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…However, studies done on other canal systems around the world indicate that canal habitats are very similar to lowland river habitats, and can in fact support a wide variety of species (Arlinghaus et al 2002;Borcherding et al 2002;Poulet et al 2005). This was clear in our study, as we observed 17 of the 30 species of fish commonly found in the Ottawa region (Poulin 2001).…”
Section: Discussionsupporting
confidence: 74%
“…However, studies done on other canal systems around the world indicate that canal habitats are very similar to lowland river habitats, and can in fact support a wide variety of species (Arlinghaus et al 2002;Borcherding et al 2002;Poulet et al 2005). This was clear in our study, as we observed 17 of the 30 species of fish commonly found in the Ottawa region (Poulin 2001).…”
Section: Discussionsupporting
confidence: 74%
“…Differences in feeding habits among sites were influenced by the presence of riparian vegetation. It is known that processes that occur in riparian zones influence the aquatic biota (GREGORY 1992, PUSEY & ARTHINGTON 2003 and lead to changes ZOOLOGIA 27 (2): 191-200, April, 2010 in the diet of different fish species (see WAITE & CARPENTER 2000, FERREIRA et al 2002, reinforcing its importance as a buffer zone (BOJSEN & BARRIGA 2002, SWEENEY et al 2004, POULET et al 2005. It is important to mention that the presence of arboreal riparian vegetation, even in poor state of conservation, provided distinct feeding resources to the fish fauna, reinforcing the findings of a previous study carried out by the authors of this paper (CENEVIVA-BASTOS & CASATTI 2007).…”
Section: Discussionmentioning
confidence: 99%
“…But, further improvement of water quality, with increased water clarity, may be unfavourable to European pikeperch as this species prefers deep ( i.e. dark) or turbid waters (Poulet et al , 2005).…”
Section: Discussionmentioning
confidence: 99%